PENGARUH PRODUK WISATADAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERKUNJUNG MELALUI ELECTRONIC WORD OF MOUTH SEBAGAI VARIABEL INTERVENING (Studi pada Pengunjung Objek Wisata Goa Pindul Yogyakarta) - Rizka Iqbal Putranegara; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2016)
The tourism industry in a number of areas is increasing, its specialty in Yogyakarta Province. Goa Pindul attractions in Yogyakarta has a unique tourism potential with beautiful stalactites and stalagmites cave tubing rides. The number of tourist arrivals from 2010 to 2015 the number fluctuates. This study aims to determine the influence of the tourism product and service quality to the decision been through word of mouth on the electronic attractions Pindul Goa. This type of research is explanatory research, with data collection through questionnaires and interviews. The sampling technique uses accidental sampling method. The sample in this study amounted to 100 respondents who are visitor attractions Goa Pindul and obtain information via the Internet. The results showed that the Tourism Product and significant effect on the Electronic word of mouth. Service Quality and significant effect on the Electronic word of mouth. Electronic word of mouth influence and significant to the Decision of Been. Tourism products have the most influence dominan.Hasil is obtained by analyzing primary data using validity, reliability test, correlation coefficient, simple regression analysis, coefficient of determination, significance test (t test) in both directions. Based on this, the researchers suggest that managers Attractions Goa Pindul further enhance the tourism product and service quality, which is clear signpost the way to Goa Pindul, increase the comfort of attractions Goa Pindul, improve services to visitors, so as to increase tourist arrivals in the tourist attraction Goa Pindul.